Regenerative Endodontic Treatment of Maxillary Incisors with a History of Severe Traumatic Injury - Nazanin Chitsaz; Mehrfam Khoshkhounejad; Hadi Assadian; Behnam Bolhari; Mohammadreza Sharifian; Zahra Mohammadi (Case Reports in Dentistry)
The treatment objective for children with avulsed anterior teeth should concentrate on preserving the alveolar bone volume and contour. Posttraumatic external inflammatory root resorption (EIRR) is also a high-risk complication often observed in children. Regenerative endodontic procedure (REP) has been considered a successful treatment to arrest EIRR, especially in posttraumatic cases. This case report presents clinical outcomes of REP in two teeth of an 8-year-old systemically healthy patient with a history of severe dentoalveolar traumatic injury, one with a history of avulsion, and the other with an EIRR. The treatment consisted of REP on both teeth #8 and #9. The results showed some evidence of maturation in the apical third of tooth #9 and resolution of signs and symptoms on tooth #8.